Strategia urzeczywistniania w Polsce koncepcji gospodarki opartej na wiedzy - Kuźniar, Katarzyna (The strategy of realizing knowledge-based economy idea in Poland, 2006)
The main purpose of the article is to propose the outline of the strategy of realizing knowledgebased economy idea in Poland. The author analyzes this strategy on the basis of selected examples: Silicon Valley and Singapore - these economies are found knowledge-based. It is also an attempt of answering the question: is it possible to create knowledge-based economy in postcommunist countries, which should still deepen so called first transformation.
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2006; nr 1131, s. 184-197